Profil peresepan antibiotik golongan penisilin di apotek sakti farma periode januari 2020-maret 2020 - Nur Farahim (Universitas Islam Madura, 2021)
The penicillin class is the most basic antibiotic used for patients with infections because it has a low spectrum or is simpler to inhibit bacterial growth. This study aims to obtain profile data on antibiotic prescription at the Sakti Farma Pharmacy, Bangkalan, January-March 2020. This research was conducted at the Pharmacy. Sakti Farma Bangkalan. The method used in this study was descriptive and carried out retrospectively, the population in this study were all patient prescriptions that entered the Sakti Farma Pharmacy January-March 2020, a total of 372 recipes and data taken and used as samples For the January-March 2020 period, there were 163 prescriptions that had penicillin class antibiotics in them and met the inclusion criteria. The data could be analyzed by means of descriptive analysis. The results showed that the percentage of antibiotic use in the January-March 2020 period was quite high, namely (43 , 81%.) Percentage The most commonly prescribed use of penicillin class antibiotics is amoxicillin as much as 84.66% and only as much for ampicillin drugs (15.33%.) The percentage of doses used for penicillin class of antibiotics that are most often used is amoxicillin 3x500mg as much (67.48%) The highest percentage of use of penicillin class antibiotics by sex was in women (58.9%). The highest percentage of use of penicillin class antibiotics by age was in adult patients (82.82%). The percentage of use of penicillin class antibiotics was based on dosage form The most widely used preparation was in caplet form (47.85%). The highest use of penicillin class antibiotics was for the therapy of ISPA, namely as many as 131 prescriptions (80.36%) and for dental and oral problems as many as 25 prescriptions (19.63%).